PHYTOCHEMICAL ANALYSIS OF CRUDE EXTRACTS FROM ANNONA SENEGALENSIS (L) AND ITS ANTI-SNAKE VENOM POTENTIAL ON ALBINO RATS - Musa, D. D.; Anakaa, T. M.; Bashir, K. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This work seeks to determine the phytochemical analysis of crude extracts from Annona senegalensis (L) and its anti-snake venom potential on albino rats, the plant part (stem) was collected using cutlass, air-dried, pulverized into powder using mortar and pestle,the powdered sample was soaked using cold maceration method. Two black-necked spitting cobra were captured and their venom milked by holding the snake at the head region using a conical flask covered with a black polythene and the snake brought closer to the flask such that any bite on the covered flask allows for the collection of the venom. Phytochemical screening of petroleum ether and ethanol crude extracts of A. senegalensis revealed the presence of alkaloids, flavonoids, saponins, glycosides and tannins. The lethal dose of snake venom capable of killing 50% of the rats was observed to be 0.194mg/ml among other concentrations (0.240mg/ml, 0.068mg/ml and 0.036mg/ml) administered. The effective dosages of petroleum ether and ethanol extracts of A. enegalensis needed for survival of venom injected rats are 75mg/ml and 100mg/ml respectively. This study showed that A. senegalensis possesses bioactive ingredients that have the potential to be used in managing black neck spitting cobra snakebites.